2021
DOI: 10.4103/ajps.ajps_17_18
|View full text |Cite
|
Sign up to set email alerts
|

A Useful Tip for Preventing Surgical Site Infections after Hypospadias Repair. A Single Surgeon's Experience of 376 Cases

Abstract: Purpose: We report the efficacy of pre- and post-operative showering for preventing surgical site infections (SSIs) and urethrocutaneous fistula after hypospadias surgery. Materials and Methods: In 2006, standardised pre- and postoperative showering was introduced for hypospadias patients. Showering involves washing the genitals and groin 2 h preoperatively as well as immediately after the removal of a stent postoperatively. Data from 520 procedures performed on 376 hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…During a controlled trial, Roth et al 27 randomised seventy patients with mid-shaft or distal hypospadias who received either trimethoprim-sulfamethoxazole postoperatively or no antibiotic prophylaxis and found that antibiotic prophylaxis significantly decreased the incidence of asymptomatic bacteriuria but had no role in the prevention of other postoperative complications. Murakami et al 28 assessed the role of preoperative and postoperative showering in the prevention of complications for 376 patients who underwent hypospadias repair by the same surgeon and found significantly fewer surgical site infections on the showering arm (P=0.023) and a low overall complication rate (P=0.0019); however, no significant difference in the urethral fistula rate was observed (P=0.081). They recommended that patients should shower two hours preoperatively, immediately after urethral stent removal, and after defecation to reduce the risk of complications after hypospadias repair.…”
Section: Discussionmentioning
confidence: 99%
“…During a controlled trial, Roth et al 27 randomised seventy patients with mid-shaft or distal hypospadias who received either trimethoprim-sulfamethoxazole postoperatively or no antibiotic prophylaxis and found that antibiotic prophylaxis significantly decreased the incidence of asymptomatic bacteriuria but had no role in the prevention of other postoperative complications. Murakami et al 28 assessed the role of preoperative and postoperative showering in the prevention of complications for 376 patients who underwent hypospadias repair by the same surgeon and found significantly fewer surgical site infections on the showering arm (P=0.023) and a low overall complication rate (P=0.0019); however, no significant difference in the urethral fistula rate was observed (P=0.081). They recommended that patients should shower two hours preoperatively, immediately after urethral stent removal, and after defecation to reduce the risk of complications after hypospadias repair.…”
Section: Discussionmentioning
confidence: 99%